НЕЙРОСТИМУЛЯЦІЙНІ ТЕХНОЛОГІЇ У ЛОГОПЕДИЧНІЙ ПРАКТИЦІ З ДІТЬМИ ДОШКІЛЬНОГО ВІКУ З ТЯЖКИМИ ПОРУШЕННЯМИ МОВЛЕННЯ - Наталія Лопатинська (International Journal of Innovative Technologies in Social Science, 2020)
Article reveal practical need for integration and accumulation of the knowledge in neurology, neurophysiology, neuroanatomy, neurochemistry, neuropsychology, neuropsycholinguistics for reorientation of modern logopedic practice in a narrow-disciplinary discipline. An attempt has been made to generalize the multidisciplinary research of scientists and practitioners devoted to the problems of the search for neurostimulation technologies. Author's disclosure of the experience of using modern neurostimulation technologies: neurophysiotherapy, neuroacoustic, neurologic is becoming a particular relevance. According to the results of the dynamics analysis of electrophysiological, psychological and logopedic indicators after the practical introduction of neurotechnology, positive changes in the functional state of the brain were confirmed, which contributed to the activation of the neural networks of the speech and communicative mechanism. It is generalized that the use of neurostimulation technologies in preschool-age children with different types of speech dysontogenesis is a new step in optimizing the process of children speech correction and a prerequisite for further use of classical techniques of speech therapy and steps in reaching the maximum possible results.